Paricalcitol versus Calcitriol + Cinacalcet for the Treatment of Secondary Hyperparathyroidism in Chronic Kidney Disease in China: A Cost-Effectiveness Analysis - Zhuolin Zhang; Lele Cai; Hong Wu; Hong Wu; Xinglu Xu; Wenqing Fang; Xuan He; Xiao Wang; Xin Li; Xin Li; Xin Li (Frontiers Media S.A., 2021)
Background: Chronic Kidney Disease (CKD) is a global chronic disease with increasing prevalence in recent years, particularly CKD accompanied by Secondary Hyperparathyroidism (SHPT) leads to reduced quality of life, increased mortality, a considerable economic burden for patients and society. The aim of this study was to investigate the cost-effectiveness analysis of paricalcitol vs. calcitriol + cinacalcet for CKD patients with SHPT in China in 2020.Methods: A Markov model was conducted employing data derived from published literature, clinical trials, official sources, and tertiary public hospital data in China, based on a 10-year horizon from the perspective of the healthcare system. Calcitriol + Cinacalcet was used as the reference group. CKD stage 5 (CKD-5) dialysis patients suffering from SHPT were included in the study. Effectiveness was measured in quality-adjusted life years (QALYs). The discount rate (5%) was applied to costs and effectiveness. Sensitivity analysis was performed to confirm the robustness of the findings.Results: The base case analysis demonstrated that Patients treated with paricalcitol could gain an increase in utility (0.183 QALYs) and require fewer expenditures (6925.612 yuan). One-way sensitivity analysis was performed to showed that impact factors were the price of cinacalcet, the hospitalization costs of patients with paricalcitol and calcitriol, the costs and utilities of hemodialysis and the costs of calcitriol, the costs of paricalcitol regardless of period. Probabilistic simulation analysis displayed when willingness-to-pay was ¥217113, the probability that Paricalcitol was dominant is 96.20%.Conclusion: The results showed that paricalcitol administrated to treat patients diagnosed with Secondary hyperparathyroidism in Chronic Kidney Disease, compared to calcitriol and cinacalcet, might be dominant in China.